PERSPEKTIF EKONOMI ISLAM SEBAGAI KEBANGKITAN SUMBER DAYA KEHIDUPAN BANGSA DAN NEGARA (Studi Pemikiran Muhammad Nejatullah Siddiqi dan Dr. Yusuf Qardawi) - Hali Makki; Ansari Ansari (AL-ASHLAH : Jurnal Hukum Keluarga dan Hukum Islam, 2022)
This research article uses a research library of Islamic economists' thoughts, in the development of a country and society either individually or in groups, Islamic economic ethics becomes a very important role, because ethics means the creation of people's living values in the development of Islamic economy or Sharia economy. The state is present to provide welfare and security to the community through the sector of economic products and market development.